2006
DOI: 10.1016/j.jvs.2006.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release of small interfering RNA targeting midkine attenuates intimal hyperplasia in vein grafts

Abstract: These results suggest that midkine is a candidate molecular target for preventing vein graft failure. Furthermore, for clinical applications of siRNA, a single intraoperative atelocollagen-based nonviral delivery method could be a reliable approach to achieve maximal function of siRNA in vivo. This strategy may be a useful and practical form of gene therapy against human vein graft failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 47 publications
0
60
1
Order By: Relevance
“…The involvement of CCN1, an extracellular matrix-associated protein, in the development of neointimal hyperplasia is confirmed by siRNA-mediated knockdown approach (Matsumae et al, 2008). The atheroprotective role of midkine (MK), a heparin-binding growth factor, is corroborated by the use of MK-siRNA (Banno, et al, 2006). NADPH oxidase has a critical role in the development of neointimal hyperplasia and restenosis due to its contribution to oxidative stress, which is blocked by siRNA specific to NOX2 gene Cybb, an important component of NADPH oxidase (J.M.…”
Section: Gene Therapymentioning
confidence: 91%
See 3 more Smart Citations
“…The involvement of CCN1, an extracellular matrix-associated protein, in the development of neointimal hyperplasia is confirmed by siRNA-mediated knockdown approach (Matsumae et al, 2008). The atheroprotective role of midkine (MK), a heparin-binding growth factor, is corroborated by the use of MK-siRNA (Banno, et al, 2006). NADPH oxidase has a critical role in the development of neointimal hyperplasia and restenosis due to its contribution to oxidative stress, which is blocked by siRNA specific to NOX2 gene Cybb, an important component of NADPH oxidase (J.M.…”
Section: Gene Therapymentioning
confidence: 91%
“…These include antisense oligonucleotides (ODNs), short segments of RNA with enzymatic activity (ribozymes) and small interfering RNAs [siRNA] (Dzau et al, 2002;J.M. Li et al, 2010;Banno, et al, 2006). A number of studies have shown that gene therapies can be targeted for reducing cholesterol levels, inflammation and thrombosis (Feldman & Isner, 1995); for upregulating apo-A1 and downregulating chemoattractant protein-1 (MCP1)receptor expression (Tangirala, 1999); transferring pleiotropic atheroprotective nitric oxide synthase [NOS] (Qian, 1999); targeting vascular redox biology through heme oxygenase-1, superoxide dismutase, catalase and glutathione peroxidase antioxidant gene therapy to attenuate oxidative stress (Van Assche, 2011); and lipid-lowering gene therapy to reduce plasma LDL levels (Grossman et al, 1995).…”
Section: Gene Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…The antisense oligonucleotide (ASODN) that targets MK has been reported to suppress the growth of tumors in nude mice [11,12] . Additionally, www.wjgnet.com siRNA or an ASODN that targets MK inhibits neointima formation [13] and renal injury after ischemia [14] . MK has been suggested to play an important role in carcinogenesis, thus MK can serve as a novel tumor marker or therapeutic target.…”
Section: Introductionmentioning
confidence: 99%